THE INFLUENCE OF LEADERSHIP, MOTIVATION AND INCENTIVES ON THE PERFORMANCE OF PERSONNEL OF THE OPERATIONS SECTION OF POLDA KEPRI - Indra Nara Persada; Maiza; Septa Diana Nabella (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2023)
This study supposed to analyze the influence of leadership, motivation and intensive on the performance of the Polda Kepri operations section personnel. the research method uses a causal model survey method using a census sampling technique, the entire population is sampled, totaling 72 people. research instruments used interviews and questionnaires. then the research results are obtained as follows: leadership has a significant effect on the performance of the kepri police operations bureau personnel with a t-count value for the leadership variable of 10.325 greater than the t-table of 1.662 and a significance value of 0.000 less than 0.05. motivation has a significant effect on the performance of personnel of the kepri regional police operations bureau with a t-count value for the motivation variable of 3.242 greater than the t-table 1.662 and a significance value of 0.000 less than 0.05. incentives have no significant effect on the performance of the kepri regional police operations bureau personnel with an incentive t-count value of 1.555 smaller than the t-table 1.662 and a significance value of 0.124 greater than 0.05. leadership, motivation and incentives together have a significant effect on the performance of the kepri regional police operations bureau personnel with an f-count value of 423.016 greater than the f-table of 2.48 and a significance level of 0.000 less than 0.05